2017
DOI: 10.1016/j.bbamem.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of lipid membrane structural and mechanical properties by a peptidomimetic derived from reduced amide scaffold

Abstract: Understanding how antimicrobial peptidomimetics interact with lipid membranes is important in battling multidrug resistant bacterial pathogens. We study the effects of a recently reported peptidomimetic on lipid bilayer structural and mechanical properties. The compound referred to as E107-3 is synthesized based on the acylated reduced amide scaffold and has been shown to exhibit good antimicrobial potency. Our vesicle leakage essay indicates that the compound increases lipid bilayer permeability. We use micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 97 publications
1
25
0
Order By: Relevance
“…The insensitivity of s 0 highlights that PrP106-126 does not markedly alter the thickness of the POPC bilayer. Using force spectroscopy measurements, we have observed a similar resilience of the bilayer thickness to the treatment of an antimicrobial peptidomimetic 46 . Interestingly, introducing ethanol to mica-supported planar bilayers caused a stark decrease of the bilayer thickness as indicated by the shifting of force curves toward smaller s 59 .…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…The insensitivity of s 0 highlights that PrP106-126 does not markedly alter the thickness of the POPC bilayer. Using force spectroscopy measurements, we have observed a similar resilience of the bilayer thickness to the treatment of an antimicrobial peptidomimetic 46 . Interestingly, introducing ethanol to mica-supported planar bilayers caused a stark decrease of the bilayer thickness as indicated by the shifting of force curves toward smaller s 59 .…”
Section: Resultsmentioning
confidence: 72%
“…S4, Supporting Information). Using fusogenic calcium ions, we have shown that lipid molecules extracted from planar bilayers can form a second layer on top of the original bilayer 46 . The process of forming a second layer is reminiscent of the formation of a mica-supported bilayer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A maximum force called the puncture force is reached when the bilayer is punctured by the tip (indicated by arrowheads in Fig. 3) [29]. For the intact bilayer, the puncture force is ~3 nN and the bilayer puncture takes place at a distance of ~4 nm away from the mica surface (located at zero distance).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously used this method to evaluate changes in bilayer permeability caused by different compounds. 3840…”
Section: Resultsmentioning
confidence: 99%